Laparoscopic attenuation of a congenital extrahepatic portosystemic shunt in a dog—a thin-film banding for splenophrenic shunt: A case report - Park, Jiyoung; Jang, Kwangsik; Jo, Hyun Min; Kim, Se Eun (Frontiers in Veterinary Science, 2022)
A 6-year-old castrated male Shih-Tzu dog weighing 6.5 kg presented with chief complaints of pollakiuria, urine dribbling, and vomiting. He had a history of urolithiasis for 3 years, which was confirmed by the presence of ammonium urate in the urinary stone analysis, performed 2 years prior to the presentation. Blood examination showed high values of fasting ammonia, postprandial bile acid, and low blood urea nitrogen. Microhepatica and urolithiasis were identified on plain radiography and ultrasonography. A computed tomography angiography demonstrated a shunting vessel, diameter up to 9.6 mm, originated from the splenic vein and linked with the phrenic vein. A surgical attenuation with a thin film banding was performed under laparoscopic visualization. Left triangular ligament was incised, and one marionette stay suture was placed to the stomach to expose the vessel. The shunting vessel was dissected before it entered the diaphragm, and a thin film band was applied around the vessel. The patient recovered uneventfully without post-attenuation neurologic signs. Portal vein diameter increased with time, and complete closure of the shunting vessel was identified on computed tomography angiography performed at 14 months after attenuation. The patient was doing well for 26 months after surgery without protein restriction. This is the first report of laparoscopic attenuation for splenophrenic type of canine congenital extrahepatic portosystemic shunt with a favorable outcome. This report supports the finding that laparoscopic attenuation is clinically practical for splenophrenic shunt in small-breed dogs.